2D visualization of terms and documents in Malay language - Tengku Sembok, Tengku Mohd; Kamal Ismail, Normaly; Mat Saad, Nur Hamizah; Sidi Omar, Sidi Bukhari (2013)
In the technology era, information is just at our fingertip. Much information nowadays can be searched in digitize way. The output of the data is still in the listed form, and this linear form (one dimension) makes user hardly to find information related to the data requested. In addition, Malay document is still displayed in textual listed form. 676 documents from Jilid 1 of Hadith Al Tarmizi in Malay language are used to visualize the relationship. Method used to develop vector space model for term-document relationship is TF*IDF and Cosine Similarity technique used for document-document relationship. While, Prefuse toolkit is used as the visualization tool. From the 2D graphic, the relationship between Hadis can be found easily. From the questionnaire conducted, 90% participants agree that more relevant documents can be found using the 2D graphics system.